Analysis and Annotation of Whole‐Genome or Whole‐Exome Sequencing Derived Variants for Clinical Diagnosis. (13th February 2018) - Worthey, Elizabeth A.
Abstract: Over the last 10 years, next‐generation sequencing (NGS) has transformed genomic research through substantial advances in technology and reduction in the cost of sequencing, and also in the systems required for analysis of these large volumes of data. This technology is now being used as a standard molecular diagnostic test in some clinical settings. The advances in sequencing have come so rapidly that the major bottleneck in identification of causal variants is no longer the sequencing or analysis (given access to appropriate tools), but rather clinical interpretation. Interpretation of genetic findings in a complex and ever changing clinical setting is scarcely a new challenge, but the task is increasingly complex in clinical genome‐wide sequencing given the dramatic increase in dataset size and complexity. This increase requires application of appropriate interpretation tools, as well as development and application of appropriate methodologies and standard procedures. This unit provides an overview of these items. Specific challenges related to implementation of genome‐wide sequencing in a clinical setting are discussed. © 2017 by John Wiley & Sons, Inc.